MARKETING STRATEGY AT START-UP COMPANY IN EDUCATION FIELD AT CV.BIG EDU INDONESIA - Maula, Nurkholifatul (Badan Penelitian dan Pengembangan Daerah (BP2D) Provinsi Jawa Barat, 2019)
Seeing the development of startups in Indonesia which is quite rapid and has expanded equally to all regions in Indonesia. However, looking at startups in the field of Edutech or education that do not exist as e-commerce startups, it has its own challenges for Indonesia. There is a startup company Edutech that is quite unique, which is engaged in research, namely CV. Big Edu Indonesia. This study aims to answer three questions, namely: business model CV. Big Edu Indonesia, marketing strategies and their impact. This research uses a qualitative descriptive approach, Miles and Huberman analysis, with in-depth interview techniques. CV. Big Edu Indonesia has research and school consulting services, and there is a Research Plan Book product. The strategies used are: content marketing on Instagram, LinkedIn, and Blogs; Opening volunteers in several areas, holding Student Ambassadors in various areas, building a Big Edu Project community on WhatsApp and Facebook, holding online discussions every month by inviting reliable speakers, and conducting short training in schools. The impact of this strategy is to increase the number of online discussion participants.